Agronomical performance of potato (Solanum tuberosum L.) cv. ´Unica´ under inoculation with native rhizobacteria and application of acetyl salicylic acid - Contreras-Liza, Sergio Eduardo; Luyo Sanchez, Luis; Zúñiga Davila, Doris Elizabeth (Revista de Ciências Agroveterinárias, 2018)
Peru is center of origin of potato and its wild relatives, so it is convenient to develop new technologies of agronomical management with less impact on the ecosystem, as in the use of pesticides and chemical fertilizers in potato is increasing in developing countries. The objective of the work was to evaluate the agronomic performance of potato cv. ´Unica´ under inoculation with PGPR rhizobacteria isolated from the rhizosphere of Andean potatoes and on the effect of the application of acetylsalicylic acid in field conditions of the Peruvian coast. Inoculation of four bacterial isolates were evaluated: Bacillus simplex B13, Bacillus amyloliquefaciens Bac 15Mb, Azotobacter sp. Azo 16M2 and Pantoea sp. DZ22, as well as a dose of 0.4 mM acetyl salicylic acid as promoter treatments for plant growth versus a control with no inoculation. A randomized complete block design was used in a sandy loam class soil, slightly alkaline, with low organic content and free of salts. There was a relative humidity between 54 and 71%, while the average air temperatures ranged between 13 and 21 °C in San Vicente de Cañete, Lima (coordinates UTM 18L3540788550372). Inoculated plants with bacterial strains at sowing time and control were evaluated at flowering in plots of 40 plants with three replications for several physiological and productive parameters. Means were separated statistically through Duncan’s multiple range test and processed with Infostat software. Inoculation with strain Azotobacter sp. Azo 16M2, showed significant differences (p<0.05) with respect to control without inoculation, increasing tuber yield and commercial tuber weight per hectare and with less damage by the leafminer fly (Liriomyza huidobrensis) vis-à-vis the control. Also application of acetyl salicylic acid showed higher percentage of inflorescences (p<0.05) compared to the control, while statistical differences were not found between bacterial strains for this character. It was concluded that the application of inoculant strain Azotobacter sp. Azo 16M2 improved the agronomic performance of potato cv. ‘Unica’, under subtropical conditions of the valley of Cañete in terms of production of tubers and commercial quality, and less foliage damage by the leafminer fly compared to non-inoculated plants.